Potential role of circular RNA in cyclosporin A‐induced cardiotoxicity in rats. Issue 2 (25th May 2021) - Zhao, Yanru; Li, Yang; Fan, Dachuan; Hou, Jinxiao; Bai, Yunpeng; Dai, Chenguang; Cao, Xue; Qi, Hai; Liu, Bingchen
Abstract: Cyclosporin A (CsA) is a well‐known and effective drug that is commonly used in autoimmune diseases and allotransplantation. However, kidney toxicity and cardiotoxicity limit its use. Circular RNAs (circRNAs) play a crucial role in disease, especially cardiovascular disease. We aimed to explore the circRNA expression profiles and potential mechanisms during CsA‐induced cardiotoxicity. Sixty male adult Wistar rats were randomly divided into two groups. The CsA group was injected with CsA (15 mg/kg/day body weight) intraperitoneally (ip) for 2 weeks, whereas the control group was injected ip with the same volume of olive oil. We assessed CsA‐induced cardiotoxicity by light microscopy, transferase‐mediated dUTP nick‐end labeling (TUNEL) staining, and electron microscopy. Microarray analysis was used to detect the expression profiles of circRNAs deregulated in the heart during CsA‐induced cardiotoxicity. We confirmed the changes in circRNAs by quantitative PCR. Moreover, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses of the microarray data were performed. A conventional dose of CsA induced cardiotoxicity in rats. We identified 67 upregulated and 37 downregulated circRNAs compared with those in the control group. Six of 12 circRNAs were successfully verified by quantitative real‐time polymerase chain reaction (qRT‐PCR). GO analyses of the differentially expressed circRNAs indicated that these molecules might play important roles in CsA‐induced cardiotoxicity. KEGG pathway analyses showed that the differentially expressed circRNAs in CsA‐induced cardiotoxicity may be related to autophagy or the Hippo signaling pathway. We identified differential circRNA expression patterns and provided more insight into the mechanism of CsA‐induced cardiotoxicity. CircRNAs may serve as potential biomarkers or therapeutic targets of CsA‐mediated cardiotoxicity in the future. Abstract : Multiple circRNAs were deregulated during CsA‐induced cardiotoxicity. A conventional dose of CsA could induce cardiomyocyte toxicity in rats. Differentially expressed circRNAs were related to autophagy or the Hippo signaling pathway in CsA‐induced cardiotoxicity. Our study could help elucidate the molecular mechanisms of CsA‐mediated cardiotoxicity. CircRNAs may serve as potential biomarkers or therapeutic targets of CsA‐mediated cardiotoxicity in the future.